2010
DOI: 10.1007/s10393-010-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of the Lyme Disease Vector Ixodes scapularis: Implications for Borrelia burgdorferi Endemicity

Abstract: Lyme disease risk is increasing in the United States due in part to the spread of blacklegged ticks Ixodes scapularis, the principal vector of the spirochetal pathogen Borrelia burgdorferi. A 5-year study was undertaken to investigate hypothesized coinvasion of I. scapularis and B. burgdorferi in Lower Michigan. We tracked the spatial and temporal dynamics of the tick and spirochete using mammal, bird, and vegetation drag sampling at eight field sites along coastal and inland transects originating in a zone of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 59 publications
8
139
1
2
Order By: Relevance
“…31 Similarly, increasing ranges for I. scapularis have been documented along the Hudson River Valley, Michigan, and Virginia. [32][33][34] Comparing the maps presented here with our previous surveillance summary from 2000 to 2007, anaplasmosis appears to be increasing in geographic range as well as in IR, consistent with changes in the range of its tick vector. 30 More cases were reported during 2008-2012 than during 2000-2007; and, analysis of human data in tandem with ecological data may elucidate changing risk of exposure to human populations.…”
Section: Methodssupporting
confidence: 77%
“…31 Similarly, increasing ranges for I. scapularis have been documented along the Hudson River Valley, Michigan, and Virginia. [32][33][34] Comparing the maps presented here with our previous surveillance summary from 2000 to 2007, anaplasmosis appears to be increasing in geographic range as well as in IR, consistent with changes in the range of its tick vector. 30 More cases were reported during 2008-2012 than during 2000-2007; and, analysis of human data in tandem with ecological data may elucidate changing risk of exposure to human populations.…”
Section: Methodssupporting
confidence: 77%
“…Using this threshold, the final model had 91% accuracy, 93% sensitivity, and 90% specificity. The model predicted the presence of infected nymphs in some negative sites for which other sources indicate emerging risk, such as eastern Maine, 30 the Illinois/Indiana border, 24,31 the New York/Vermont border, 32 southwestern Michigan, 33 and eastern North Dakota (Vaughan J, personal communication). The density of infected nymphs was often underestimated by the model in these regions, and bootstrap CIs often included the threshold value for infected nymphs, therefore the sites could not be assigned to a 95% confidence risk category.…”
Section: Discussionmentioning
confidence: 99%
“…Uninfected I. scapularis populations were also identified along two of these putative expansion fronts (Illinois/Indiana and New York/Vermont), consistent with a pattern of initial tick spread followed by the spread of B. burgdorferi. 34 An alternative invasion pattern was detected in Michigan, 33 where low-prevalence B. burgdorferi infection was detected in other tick species and in wildlife at inland sites before the arrival of I. scapularis. The authors suggested a cryptic B. burgdorferi transmission cycle by other vectorcompetent tick species in the absence of I. scapularis.…”
Section: Discussionmentioning
confidence: 99%
“…The myriad of tick species and wide variety of tick lifestyles makes them difficult to control in domestic animals, and their ability to survive adversity allows them to successfully follow their hosts into new and diverse habitats. Those traits, along with other factors such as habitat destruction, climate change, and pet portability, will likely increase encounters between ticks and pets in the future (Bacon et al 2008;Chomel 2011;Diuk-Wasser et al 2012;Hamer et al 2010). New information is continually being learned regarding tick-borne diseases in the medical and veterinary communities.…”
Section: Introductionmentioning
confidence: 99%